The Punishment Of Misbruik Van Omstandigheden As A Basis For Determining Workers' Wages - Dharma Setiawan Negara*; Lufsiana Lufsiana; Samuel Dharma Putra Nainggolan (Riwayat: Educational Journal of History and Humanities, 2023)
Even though the employment relationship between workers and employers is regulated in the Labor Law regime so that it can be equal, in practice this is not the case. The superiority of employers as employers often places workers in an unfavorable situation. Sometimes it is very apparent that workers need more entrepreneurs to live their lives through the wages they receive, compared to employers who need workers to carry out their business. This could be a sign that wages are below the minimum wage set by the government. This research is legal research that examines this unequal reciprocal relationship in practice, Use legal, conceptual and case-based approaches to draw conclusions and determine penalties for employers who pay workers below the minimum wage.